Localized‐domains staging structure and evolution in lithiated graphite. Issue 1 (2nd June 2022) - Weng, Suting; Wu, Siyuan; Liu, Zepeng; Yang, Gaojing; Liu, Xiaozhi; Zhang, Xiao; Zhang, Chu; Liu, Qiuyan; Huang, Yao; Li, Yejing; Ateş, Mehmet N.; Su, Dong; et al.
Abstract: Intercalation provides to the host materials a means for controlled variation of many physical/chemical properties and dominates the reactions in metal‐ion batteries. Of particular interest is the graphite intercalation compounds with intriguing staging structures, which however are still unclear, especially in their nanostructure and dynamic transition mechanism. Herein, the nature of the staging structure and evolution of the lithium (Li)‐intercalated graphite was revealed by cryogenic‐transmission electron microscopy and other methods at the nanoscale. The intercalated Li‐ions distribute unevenly, generating local stress and dislocations in the graphitic structure. Each staging compound is found macroscopically ordered but microscopically inhomogeneous, exhibiting a localized‐domains structural model. Our findings uncover the correlation between the long‐range ordered structure and short‐range domains, refresh the insights on the staging structure and transition of Li‐intercalated/deintercalated graphite, and provide effective ways to enhance the reaction kinetic in rechargeable batteries by defect engineering. Abstract : The microstructure of Li + ‐graphite intercalation compounds (GIC) was directly visualized by cryo‐transmission electron microscopy with minimized artifacts. Each macroscopical staging compound is a mixture of different staging phases and dislocations. It is long‐range order, medium‐range disorder, and short‐range order, which is much different from the previously proposed Rüdorff‐Hofmann and Daumas‐Hérold models. Localized‐domains model is proposed to describe the real structural nature of the Li + ‐GIC.